Decision Support System for Food Menu Selection at Engineering Faculty Canteen 3 Using the SAW Method: Decision Support System for Food Menu Selection Using the SAW Method - Dwi Aura Ningrum; M Rizky Subagia Ramadhan; Sri Rezeki Candra Nursari (bit-Tech, 2026)
Students often face challenges when selecting food from cafeteria menus due to the need to consider multiple criteria simultaneously, including price, taste, and portion size. To address this issue, this study develops a Decision Support System (DSS) for menu selection at Canteen 3 of the Faculty of Engineering, Universitas Pancasila, using the Simple Additive Weighting (SAW) method. The primary contribution of this research lies in enhancing the objectivity and consistency of daily food selection decisions among students through a quantitative, criteria-based approach. The SAW method is employed due to its simplicity and effectiveness in multi-criteria decision-making problems. Three main criteria are applied: price (C1), taste (C2), and portion size (C3). Each menu alternative is evaluated, normalized, and weighted to obtain a final preference score. The results indicate that Indomie achieves the highest score of 100, primarily due to its favorable balance between affordable price, acceptable taste, and sufficient portion size, followed by Spaghetti with a score of 88.875. These findings demonstrate that the SAW-based DSS is capable of producing objective and efficient menu recommendations that align with student preferences. Furthermore, the proposed system has the potential to be applied in other cafeterias or faculties within the campus environment, thereby supporting broader decision-making processes. Future research is encouraged to incorporate additional criteria and more diverse menu alternatives to further improve system accuracy and applicability.